HUBUNGAN KARAKTERISTIK, MOTIVASI DAN KOMPETENSI TERHADAP PRODUKTIVITAS KERJA PENYULUH PERTANIAN DI KOTA BENGKULUHUBUNGAN KARAKTERISTIK, MOTIVASI DAN KOMPETENSI TERHADAP PRODUKTIVITAS KERJA PENYULUH PERTANIAN DI KOTA BENGKULU - Hanafiah, M. Ali; Rasyid, Witman; Purwoko, Agus (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
The objective of this research is to analyze the correlation of the agricultural agents’ characteristics, motivation and competence to their work productivity. This research was conducted in February through April 2013 and used census methods. The study population was defined as many as 33 people of 45 people from the extension of existing civil servants. Data analysis was done by using Product Moment Pearson procedure. The results showed that: 1) some of the agents’ characteristics were correlated significantly with their job productivity, there were period of employment, training, agricultural area in the region of agriculture extension, 2) Some factors of the agents’ motivation were correlated significantly with their job productivity. There are recognition, salary and reward. 3) Some factors of the agents’ competencies were correlated significantly with their job productivity. There are planning, implementating, evaluation of agriculture extension, and communication skills real contact with the work productivity of agricultural extension. 4) Work productivity level of agricultural extension agents still not yet good (“low” category) because four of five factors work productivity as method extension, extension materials and increased knowledge and skills of farmers were low.